Hubungan Pengetahuan, Situasi, Sikap Dan Motivasi Dengan Keputusan Pembelian Laptop - Bruno Hami; V. Ratna Inggawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2018)
The study aims to obtain empirical information that knowledge, situation, attitude and motivation have positive relationship simultaneously and partially with laptop purchasing decision from students of Economic Faculty of Catholic University Darma Cendika Surabaya. Problems and hypothesis are formulated based on references and empirical studies. To test the hypothesis used regression conversion F test (linearitan) to determine whether the relationship between the dependent variable with the independent variable is linear or not. The correlation coefficient test is used to determine the size of the correlation coefficient whether significant or not. Population in this research is students of Economic Faculty of Catholic University Darma Cendika Surabaya with amount of sample counted 100 people. The end result of the study shows that the partial correlation test shows: (i) knowledge has a correlation coefficient of 0,034 with significance of 0,738 > 0,05, meaning the correlation coefficient is not significant; (ii) the situation has a correlation coefficient of 0,365 with significant 0,00 < 0,05, meaning significant correlation coefficient; (iii) attitude of having correlation coefficient 0,416 with significance 0,00 < 0,05, meaning significant correlation coefficient; and (iv) motivation has a correlation coefficient of 0,232 with a significance of 0,022 < 0,05, meaning the correlation coefficient is significant. Simultaneously, the dependent variable relation (X) with independent variable (Y) is positive with adjusted R Square (R2) of 0,428 which means that 42,8% purchase decision of laptop students of Economic Faculty of Catholic University Darma Cendika Surabaya can be explained by the four dependent variables, while the remaining 57,2% of the decision to purchase laptop students of Economic Faculty of Catholic University Darma Cendika Surabaya can be explained by other variables outside of the four dependent variables currently being studied.